Promoting equity in educational centres: to identify learning and participation obstacles in order to foster a more inclusive education - de Haro Rodríguez, Remedios; Ayala de la Peña, Amalia; Del Rey Gil, María Victoria (Revista Complutense de Educación, 2020)
One of the goals proposed by the UNESCO (2015), in the proclamation of the 2030 Agenda for Sustainable Development, is to promote an inclusive, equitable and quality education for everyone. In order to foster this type of education, it is necessary to identify the learning and participation obstacles present in the educational centres, with the aim of removing them and establishing processes of change and improvement intended to achieve that goal.This paper shows the results obtained in a study aimed at distinguishing the barriers to inclusion present in the educational centres of a town in the Region of Murcia (Spain). The research design implemented is descriptive, in the form of a survey, and it is aimed at providing information related to the current situation in order to subsequently take decisions. The sample is made up of five Compulsory Education centres located in the town of Torre Pacheco, specifically 122 teachers have taken part. The tool for the data gathering has been an ad-hoc questionnaire, formed by three dimensions (educational context, educational resources and educational process). The results of this paper evidence obstacles which restrict the students’ access and learning opportunities regarding the educational context, resources and processes of the studied centres, as well as meaningful differences in the identification of such barriers, based on the educational stage in which teachers perform their work and on the centre ownership. As a conclusion, it is necessary to highlight how important it is to identify such obstacles, so that processes of change and improvement of the educational reality can be implemented, allowing to achieve a better education for everyone, more equitable and, consequently, inclusive.
Keywords: inclusion; quality of education; teaching practice; educational improvement; compulsory education